HVSR analysis of seismic site effects and soil-structure resonance in Varaždin city (North Croatia). Issue 92 (January 2017) - Stanko, Davor; Markušić, Snježana; Strelec, Stjepan; Gazdek, Mario
Abstract: Varaždin is an old baroque city located in the North of Croatia along the Drava River basin (alluvial sediments). Local site effects due to alluvial soft sediments (clays, sands, gravels) can play a crucial role in the amplification of seismic wave ground motions. Ambient noise (microtremors) measurements using the Horizontal-to-Vertical Spectral Ratio (HVSR) method were applied to determine the seismic ground response of the area, expressed by the fundamental/natural frequency ( f 0 ) and the site amplification ( A 0 ) of the sediments. The results of the free-field measurements show variations of the soil fundamental frequencies (0.47–5.19 Hz), site HVSR amplifications (1.95–4.65), Vs, 30 distributions (212–340 m/s) and the sediments cover thicknesses (16–116 m) above bedrock in Varaždin city area. The obtained results are found in good agreement with the geological map, the thicknesses of the sediments from lithological cross sections, existing boreholes data and MASW measurements. It was observed that the directional HVSR analysis and the polarization angles of the microtremors are affected by the horizontal polarization of the ground motion near, along and across the faults and correspond to the earthquake mechanism of the fault-plane solution from the past earthquakes in the area. The potential danger of the soil-structure resonance was estimated by comparison of the microtremor measurements in buildings of different heights (3–11 floors) and nearby free-field locations, using the Standard Spectral Ratio and Floor Spectral Ratio. The fundamental frequency of buildings ranged from 1.78 Hz for taller buildings up to 5.64 Hz for smaller buildings. If the building fundamental frequency is close to the soil fundamental frequency, the seismic ground motion will create possible resonance. Smaller buildings up to 6 floors showed lower potential of soil-structure resonance due to very low soil fundamental frequencies for the entire city area, while taller buildings up to 11 floors showed higher potential of soil-structure resonance. The directional HVSR analysis demonstrated how buildings in the studied area receive majority of the ambient noise energy from the polarization direction which is comparable with the observed polarization angles from free-field measurements. The microtremor HVSR method proved to be useful for estimation of seismic site effects and the potential danger of soil-structure resonance in an area with low seismicity like Varaždin city. Presented results are of great importance concerning monumental heritage and urban planning in Varaždin city. Highlights: Local site effects and soil-structure resonance in Varaždin city was studied. The microtremor HVSR method was used to determine seismic ground response. Microtremor measurements were performed in buildings of different floors. Possible danger of soil-structure resonance was determined in Varaždin city area. Ambient noise is affected by fault zones in alluvial sediments.